Efficient chemical regeneration of LiBH4NH3 spent fuel for hydrogen storage. (5th January 2015) - Tan, Yingbin; Chen, Xiaowei; Xia, Guanglin; Yu, Xuebin
Abstract The absence of an efficient method for the regeneration of ammine metal borohydrides (M(BH4)nxNH3, AMBs) from their dehydrogenated products has hindered their potential application as hydrogen storage materials. In this paper, we demonstrate a high-yield chemical regeneration of LiBH4NH3 based on a three step process (digestion (H+ addition), reduction (H− addition), and ammonia complexation) at ambient temperature. Our results demonstrated that Li–B–N polymer was digested by methanol to form LiB(OCH3)4, which can be converted into LiBH4 by using LiAlH4 in the reduction process. The generation of LiBH4NH3 in ammonia complexion step was achieved by exposing the obtained LiBH4 in an ammonia atmosphere.